Analysis of the Limitation of the Attribution Authority of the Director Gen-eral of Customs and Excise in the Redetermination of the Classification of Imported Goods Based on the Customs Law - Francis Maryanne Pattynama; Sylvia Setjoatmadja; Suyanto Suyanto (LEGAL BRIEF, 2026)
This study analyzes the limits of the attribution authority of the Director General of Customs and Excise in the redetermination of the classification of imported goods based on Law Number 10 of 1995 concerning Customs as amended by Law Number 17 of 2006 (hereinafter referred to as the Customs Law). The classification of goods is an important element in customs administration that determines the amount of import duties, taxes, and potential licensing. The authority of the Director General of Customs and Excise in re-establishing the classification of imported goods, especially as stipulated in Article 17 of the Customs Law, has significant implications for legal certainty and compliance of business actors. This study aims to identify the scope, limitations, and legal implications of attribution authorities. Using normative legal research methods with legislative and conceptual approaches, this study examines various relevant laws and regulations and legal literature. The results of the study show that the attribution authority of the Director General of Customs and Excise in the reclassification of imported goods comes from Article 17 of the Customs Law, which provides a legal basis for making classification adjustments if there are differences. However, this authority is not absolute and is limited by the principles of administrative law. The implications of the reclassification include potential changes in import duty rates and the emergence of customs disputes. The study recommends the need for further clarity on the implementation of Article 17 of the Customs Law, as well as strengthening the monitoring mechanism.